Profil Noda Ekstrak Kloroform : Metanol (2:1) dan Aktivitas Bslt Kulit Batang Nyirih (Xylocarpus Granatum) - Surmadi Sumardi; Nilsya Febrika Zebua; Vriezka Mierza; Reihan Maurani Arafah; Qhairunnisa Qhairunnisa; Riska Amalia (Journal of Pharmaceutical and Health Research, 2023)
Nyirih plants (Xylocarpus granatum) grows along the edge of the sea, and in other salty environments. Chemical compounds contained in the bark of the betel nut (Xylocarpus granatum) include alkaloids, triterpenoids, steroids, saponins, and flavonoids. The content of lipid compounds in the bark of betel nut (Xylocarpus granatum) has not been widely studied, including toxicity to cells. This study aims to determine the profile of stains on the bark extract of nyirih (Xylocarpus granatum) and to determine the toxicity of the bark extract of nyirih (Xylocarpus granatum). This research method is experimental which includes the manufacture of betel nut bark extract (Xylocarpus granatum) using maceration method with Chloroform:Methanol (2:1) solvent. The stain profile of Nyirih Stem Bark (Xylocarpus granatum) extract was characterized by Thin Layer Chromatography with n-Hexana:Ethyl Acetate as eluent (7:3). Nyirih Bark Extract (Xylocarpus granatum) was tested for toxicity by the Brine Shrimp Lethality Test (BSLT) method. Nyirih Stem Bark Simplisia (Xylocarpus granatum) 630 grams yielded 90 grams thick extract with a yield percentage of 14,28%. The results of the thin layer chromatography test showed that the stain profile visually produced 3 spots, UV 254 nm light had 5 spots, and UV 366 nm light had 4 spots. The LC50 value of coroform:methanol extract of betel nut bark (Xylocarpus granatum) using probit analysis was 130,7 µg/ml so it was classified as toxic and has the potential to be developed as cytotoxic.